Chitosan-pectin multiparticulate systems associated with enteric polymers for colonic drug delivery - Oliveira, Giselle F. [UNESP]; Ferrari, Priscileila C. [UNESP]; Carvalho, Livia Q. [UNESP]; Evangelista, Raul Cesar [UNESP] (Elsevier B.V., 2010)
The great challenge in using native degradable polysaccharides for the development of drug delivery systems is their high aqueous solubility, which may contribute to the undesirable premature and localized release of the drug. Multiparticulate systems showing simultaneously specific biodegradability and pH-dependent drug release were prepared based on chitosan (CS), amidated pectin (PC), and calcium ions, using triamcinolone (TC) as model drug. Hidroxypropylmethyl cellulose phthalate (HPMCP) and cellulose acetate phthalate (CAP) were successfully incorporated into the system and aided the target action of the carbohydrates. Particles were characterized for size distribution, morphology, swelling behavior and dissolution tests in media simulating the gastrointestinal tract. The addition of CAP and HPMCP resulted in the highest control over the drug release in all media. CAP:TC formulation presented the slowest drug release rate, of only 1.33%, in acidic medium after 2 h, while the control formulation released 45.52% after the same time. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Calcium pectinate; Chitosan; Colonic drug delivery; Multiparticulate system; Enteric polymers